2016
DOI: 10.3920/bm2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of bifidobacteria survival by Williopsis saturnus var. saturnus in milk

Abstract: The viability of three strains of probiotic Bifidobacterium lactis that were inoculated into UHT milk was examined with and without the presence of the yeast, Williopsis saturnus var. saturnus NCYC 22, in polypropylene tubes at 30 C. The B. lactis viable cell count for strains HN019 and BB-12 remained above 6.0 Log cfu/ml, while strain B94 had 5.7 Log cfu/ml after six weeks of incubation in the presence of the co-inoculated yeast. Incubating the bifidus milk without added yeast under anaerobic condition did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
3
0
6
Order By: Relevance
“…Enumeration of B. lactis and yeasts was performed by the plate count method according to the method of Yeo et al (2016). pH measurements were done using a 713 pH meter (Metrohm, Herisau, Switzerland) that was calibrated with pH 4 and 7 buffers (Merck).…”
Section: Growth Evaluation Of B Lactis Hn019 and Yeasts In Mono-and mentioning
confidence: 99%
See 2 more Smart Citations
“…Enumeration of B. lactis and yeasts was performed by the plate count method according to the method of Yeo et al (2016). pH measurements were done using a 713 pH meter (Metrohm, Herisau, Switzerland) that was calibrated with pH 4 and 7 buffers (Merck).…”
Section: Growth Evaluation Of B Lactis Hn019 and Yeasts In Mono-and mentioning
confidence: 99%
“…The yeast also prolonged the survival of the bifidobacteria in fermented milk during cold storage. Yeo et al (2016) reported that the viability of three commercial Bifidobacterium animalis subsp. lactis strains in unfermented milk was enhanced by Williopsis saturnus throughout long-term incubation at 30°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda Yeo e colaboradores demonstra que a levedura Williopsis saturnus subsp. saturnus NCYC22 possui a capacidade e aprimorar a manutenção da viabilidade de bactérias probióticas do gênero Bifidobacterium, incluindo a HN019 [67]. Alguns fatores são importantes na determinação do potencial probiótico de determinada linhagem de microrganismo, como a autoagregação, hidrofobicidade, capacidade de formação de biofilme e segurança quanto a sua utilização [68].…”
Section: Interações Entre Microrganismosunclassified
“…lactis HN019, linhagem autorizada e reconhecida no Brasil como probiótica, pela Agência Nacional de Vigilância Sanitária (ANVISA). Apesar de ser uma linhagem que resiste pouco à presença de oxigênio, optou-se por realizar a co-cultura em aerobiose, uma vez que as leveduras podem favorecer que o micro ecossistema mantenha a viabilidade das bactérias, como demonstrado por Yeo e colaboradores [67], ressaltando que HN019 pode se beneficiar na presença da levedura Williopsis saturnus subsp. saturnus em leite fermentado, mantendo-se viável mesmo em aerobiose.…”
Section: Teste De Interação Entre Leveduras E Bactériasunclassified